2022
DOI: 10.1097/bot.0000000000002404
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fibular Allograft in Proximal Humerus Fractures: A Systematic Review

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In a recent systematic review examining the role of fibular allograft in proximal humerus fractures, 11 studies were analyzed, and the authors concluded that fibular allografts reduced complications and improved radiological and clinical results. 35…”
Section: Tips To Optimize Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent systematic review examining the role of fibular allograft in proximal humerus fractures, 11 studies were analyzed, and the authors concluded that fibular allografts reduced complications and improved radiological and clinical results. 35…”
Section: Tips To Optimize Resultsmentioning
confidence: 99%
“…In a recent systematic review examining the role of fibular allograft in proximal humerus fractures, 11 studies were analyzed, and the authors concluded that fibular allografts reduced complications and improved radiological and clinical results. 35 It is the authors' preferred treatment to use fibular strut allografts in fractures with loss of medical column support and in patients with poor bone quality. Poor bone quality can be defined by the deltoid tuberosity index or the ratio between the outer and inner cortical diameter immediately above the upper end of the deltoid tuberosity.…”
Section: Supplemental Fixation Methodsmentioning
confidence: 99%
“…Patients who developed AVN either refused treatment or followed conservative treatment. 20 When the humeral head is necrotic, if the orthopaedic surgeon wants to do a shoulder replacement, reaming of the humerus canal in the presence of an existing intramedullary fibular graft is challenging because the fibula is a dense cortical bone and is typically well-integrated. Lu et al reported good results in the treatment of obsolete proximal humeral fractures with double plates.…”
Section: Advantages Of the Dual Plate Fixation Of The Proximal Humerusmentioning
confidence: 99%